A Practical Guide for Incorporating Emollients in the Treatment of Mild‐to‐Moderate Atopic Dermatitis - Mette Deleuran; Wioletta Barańska‐Rybak; Michael J. Cork; Stamatis Gregoriou; Angela Hernandez‐Martin; Giuseppe Micali; Andaç Salman; Petra Staubach‐Renz; Antonio Torrelo; Charles Velter; Anneke Andriessen; Vanja Adzovic; et al. (JEADV Clinical Practice, 2026)
ABSTRACT Emollients and cleansers are essential components in managing atopic dermatitis (AD). While international evidence‐based guidelines recommend using gentle cleansers and emollients daily as a foundational therapy for AD, implementation in practice remains suboptimal. Clinicians may require guidance in selecting the most appropriate options for their patients. This paper, tailored for non‐dermatologist healthcare providers, examines how to choose and integrate emollients into treating mild‐to‐moderate AD, providing practical recommendations for optimizing patient care.